Role of Information System Quality in Work Life Balance and Employee Performance - Gopinathan, Sharmini (2016)
The challenges of amalgamating work and family life is an evident fact due to technological advancement which enables remote working. (Kinnunen, Geurts & Mauno, 2005) In some companies abroad a well-balanced career and social obligations are enforced as part of the human resource initiatives to maintain a healthy and committed work force. This study aims to bridge the gap in the body of literature pertaining to information system quality’s impact on work life balance and employee performance in Malaysian ICT environments specifically. The goal of this project is to ascertain if work life balance has a mediating relationship between information system quality and employee performance. The objectives are to examine role of the information system quality (ISQ) in enabling employees to work away from the office thus, achieving work life balance as well as to determine the impact of work life balance (WLB) on employee performance. The research employed a positivist approach to conduct the study. An integrated outline was developed based on questionnaires and interviews with employees working in a remote environment from selected companies that has embarked on providing services in a 24/7 operations together with theories pertaining to ISQ and WLB from prior work drawing on multiple theoretical perspective from DeLone & McLean’s IS Success theory, Clark’s (2002) Work –family border theory and Kahn’s (1964) Role Stress theory.